Troll: issues discussed using Meme in mid-2018 - Anuar, Faizul Nizar; Ahmad, Fauziah; Mohamed Salleh, Sabariah (Human Resource Management Academic Research Society, 2021)
Text is polesemic, where a text is able to convey various meanings. Therefore, each individual will have different interpretations and opinions on something he or she experienced. Since a text can have a variety of meanings, therefore people may have different perceptions on the issues portrayed in memes. This study focuses on the Troll: Issues discusses using Meme in Mid 2018. Memes sharing on social media will lead to meaning construction for the reader. The objective of this study is to identify the issues discusses using meme in Mid-2018. A total of 30 types of memes were analysed using content analysis method. All meme samples were taken from the Facebook account of Si Rashid and Gags Malaysia during a period of three months from 1 May 2018 to 30 July 2018. The theory used as the analytical concept is the Media Dependency Theory by Ball-Rokeach and DeFleur. The results of the study found that the issues discussed using meme in 2018 focusing on the 14th General Election (GE-14), World Cup 2018 Hari Raya Aidilfitri Celebration. Some people will depend on media when a current issue arises for example during times of turmoil, crisis or natural disaster. An individual will rely on media to obtain the latest information on something that is happening. This situation can be attributed to the production of memes that widely shared through social media when an issue occurs inside or outside of the country.